2016
DOI: 10.1016/j.rppnen.2015.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Bronchial artery embolisation in management of hemoptysis – A retrospective analysis in a tertiary university hospital

Abstract: Our results suggest that BAE is a safe and effective treatment for acute severe and chronic recurrent hemoptysis, supporting the current literature. Besides this, bleeding recurrence was relatively high, and correlated with presence of systemic pulmonary shunting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
25
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(37 citation statements)
references
References 25 publications
5
25
0
3
Order By: Relevance
“…The most common complications after BAE included transient chest/ back pain and dysphagia which were reported in 1.4%-34.5% and 0.7%-30%, respectively (6,9,11,13,15,16,18,(22)(23)(24)(25)(26)(27). These figures were lower than those reported previously in older reviews and in studies with less than 50 patients (2,3).…”
Section: Complicationsmentioning
confidence: 73%
See 4 more Smart Citations
“…The most common complications after BAE included transient chest/ back pain and dysphagia which were reported in 1.4%-34.5% and 0.7%-30%, respectively (6,9,11,13,15,16,18,(22)(23)(24)(25)(26)(27). These figures were lower than those reported previously in older reviews and in studies with less than 50 patients (2,3).…”
Section: Complicationsmentioning
confidence: 73%
“…Certain angiographic features such as: a) presence of nonbronchial systemic collaterals, b) bronchopulmonary shunting, and c) incomplete initial embolization were significantly associated with higher recurrence rates (5,12,13,22,23). While a higher recurrence rate has been reported previously in patients with pleural thickening more than 10 mm as it is associated with recruitment of nonbronchial systemic collaterals (30,31), none of the studies in this review observed a significant association between pleural thickening and recurrence.…”
Section: Outcomes Of Baementioning
confidence: 99%
See 3 more Smart Citations